The effect of smoking on respiratory functions in athletes - Aydin, Serkan (2023)
The aim of this study was to investigate the effect of smoking on respiratory functions in athletes. A total of 12 American football players with an age, height and body mass means of 22.50±1.62 years, 182.83±5.85 cm., 88.91±18.99 kg. voluntarily participated in the study. The participants were competitive players with at least five years of continuous training and competition experience. Respiratory functions of the athletes were measured with a Minispir hand-held spirometer. Forced Vital Capacity (FVC), Peak Expiratory Flow (PEF), Maximal    Voluntary Ventilation (MVV) values were measured. Data were analyzed using IBM SPSS 26 package program. Because the distribution of the data was not normal, the Mann Whitney-U test and Spearman correlation test, a nonparametric test, were used to compare the data between the smoker and non-smoker groups. The significance level was accepted as p<0.05. Although numerically positive effects were found on the respiratory function of non-smokers compared to smokers, there was no statistically significant difference or correlation relationship between the data constituting these effects. As a result, it was found that the respiratory function of American football players who smoked cigarettes was lower than that of non-smokers. In line with these results, it can be stated that smoking has a negative effect on respiratory functions.